Tumor Markers in Pancreatic Cancer: 2013 - Shah, Urvi Ajay; Saif, Muhammad Wasif (JOP. Journal of the Pancreas, 2013)
Amongst the tumor markers for pancreatic cancer CA 19-9 is being used most widely and newer clinically useful applications of this tumor marker are being researched. We will discuss four abstracts presented at the American Society of Clinical Oncology (ASCO) Annual Meeting which contribute to expanding the application of CA 19-9 measurement (Abstracts #4042, #4058, #e15082, #e15146). Image: Sequence of therapeutic interventions and subsequent mean CA19-9 measurements.